2016
DOI: 10.1371/journal.pone.0162433
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Purification and Characterization of the Collagenase ColA Expressed by Bacillus cereus ATCC 14579

Abstract: Bacterial collagenases differ considerably in their structure and functions. The collagenases ColH and ColG from Clostridium histolyticum and ColA expressed by Clostridium perfringens are well-characterized collagenases that cleave triple-helical collagen, which were therefore termed as ´true´ collagenases. ColA from Bacillus cereus (B. cereus) has been added to the collection of true collagenases. However, the molecular characteristics of B. cereus ColA are less understood. In this study, we identified ColA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 59 publications
(83 reference statements)
4
11
0
Order By: Relevance
“…In fact, ColQ1 is much more active against triple-helical collagen than ColG, the clostridial collagenase with the highest reported collagenolytic activity 12 . This is consistent with our recent report on the activity of ColA from B. cereus type strain ATCC 14579 28 and indicates that, although historically less studied and therefore much less well described, bacillial collagenases may in general be much more efficient collagenolytic enzymes than clostridial collagenases. By determination of the kinetics towards collagen and its thermally denatured variant gelatin we showed that this difference can be explained by a higher helicase activity of ColQ1.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In fact, ColQ1 is much more active against triple-helical collagen than ColG, the clostridial collagenase with the highest reported collagenolytic activity 12 . This is consistent with our recent report on the activity of ColA from B. cereus type strain ATCC 14579 28 and indicates that, although historically less studied and therefore much less well described, bacillial collagenases may in general be much more efficient collagenolytic enzymes than clostridial collagenases. By determination of the kinetics towards collagen and its thermally denatured variant gelatin we showed that this difference can be explained by a higher helicase activity of ColQ1.…”
Section: Discussionsupporting
confidence: 92%
“…While there are no reports that implicate bacillial collagenases as virulence factors in B. cereus -associated foodborne diseases, in case of B. cereus mediated endophthalmitis 32 and periodontal diseases, however, collagenases have been found in the isolates of vitreous humor and dental plaques 32 , 33 , 51 , 52 . Considering the high collagenolytic efficiency of bacillial collagenases, as shown here for ColQ1 and for B. cereus ATCC 14579 ColA 28 , we propose that these enzymes facilitate the infiltration of the target tissues by degradation of the protective surrounding extracellular matrix, which then allows the diffusion of other virulence factors into the tissue. Beecher et al 32 , for example, observed a progressive degradation of the collagenous lens capsule prior to colonization of the lens cortex by B. cereus .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…For a better understanding of the algicidal activity of B. laterosporus Bl-zj as reflected in the genome, the virulence genes, secretory proteins, transporters, and pathogen-host interaction factors were further predicted and analyzed. As expected, epsilon toxin, mosquitocidal toxin, alveolysin, lethal factor, chitinase, microbial collagenase, and various carbohydrate hydrolases and peptidases were identified, which are important virulence characteristics of bacteria in invasion and infection, as well as algicidal responses (1418).…”
Section: Announcementsupporting
confidence: 63%
“…It has been shown recently that the most important effector for this is the mature NprA protein, which is cleaved by InhA1 [ 477 ]. Additionally, the phosphatidylinositol- and phosphocholine-specific phospholipase C (PI-PLC and PC-PLC) as well as the collagenase ColA are considered as pathogenicity factors [ 105 , 110 , 478 , 479 , 480 , 481 ]. The bifunctional protein CalY, formerly known as camelysin, has been shown to play an important role in cell surface adhesion and virulence, as well as in biofilms [ 482 , 483 , 484 , 485 ].…”
Section: Further Virulence Factors and Toxinsmentioning
confidence: 99%